(untitled) (Research, Society and Development, 2020)
This paper aims to describe the importance of training teachers to assist in the effective inclusion of students with disabilities, as it is understood that Assistive Technology (AT) seeks to contribute to the autonomy and independence of students through resources that aim to improve their skills. and performance. In the scope of the project we use the software SCALA (Alternative Communication System for Literacy of People with Autism), developed with focus on autistic people. The proposal of a software with simple interface that facilitates human-computer interaction sought to promote teaching practice. The potential of the software to meet the demand of students with other special needs was also observed and from a case study activities and data collection were performed that could collaborate with the teachers in the teaching-learning process in the school environment. It becomes relevant to study the realization of the fundamental role of the teacher well qualified to act in the classroom, with an inclusive pedagogical practice that enables the conception of learning, supported by resources and means that the TA through SCALA software can offer. Continuing with this research, it is known that new Assistive Technologies will certainly contribute to future teaching-learning policies, focused specifically on the teaching practice demanded of the many evidences that we list in this work.